Production, purification and characterization of cholesterol oxidase from a newly isolated streptomyces sp. - Niwas, Ram; Singh, Vineeta; Singh, Rajbir; Tripathi, Divya; Tripathi, C. K. M. (World Journal of Microbiology & Biotechnology, 2013)
Cholesterol oxidase production (COD) by a new isolate characterized as Streptomyces sp. was studied in different production media and fermentation conditions. Individual supplementation of 1 % maltose, lactose, sucrose, peptone, soybean meal and yeast extract enhanced COD production by 80-110 % in comparison to the basal production medium (2.4 U/ml). Supplementation of 0.05 % cholesterol (inducer) enhanced COD production by 150 %. COD was purified 14.3-fold and its molecular weight was found to be 62 kDa. V-max (21.93 mu M/min mg) and substrate affinity K-m (101.3 mu M) suggested high affinity of the COD for cholesterol. In presence of Ba2+ and Hg2+ the enzyme activity was inhibited while Cu2+ enhanced the activity nearly threefold. Relative activity of the enzyme was found maximum in triton X-100 whereas sodium dodecyl sulfate inactivated the enzyme. The enzyme activity was also inhibited by the thiol-reducing reagents like Dithiothreitol and beta-mercaptoethanol. The COD showed moderate stability towards all organic solvents except acetone, benzene and chloroform. The activity increased in presence of isopropanol and ethanol. The enzyme was most active at pH 7 and 37 A degrees C temperature. This organism is not reported to produce COD.
Keywords: Affinity chromatography; Cholesterol oxidase; HPLC; SDS PAGE; Streptomyces sp.

Isolation, characterization and antifungal docking studies of wortmannin isolated from penicillium radicum - Singh, Vineeta; Praveen, Vandana; Tripathi, Divya; Haque, Shafiul; Somvanshi, Pallavi; Katti, S. B.; Tripathi, C. K. M. (Scientific Reports, 2015)
During the search for a potent antifungal drug, a cell-permeable metabolite was isolated from a soil isolate taxonomically identified as Penicillium radicum. The strain was found to be a potent antifungal agent. Production conditions of the active compound were optimized and the active compound was isolated, purified, characterized and identified as a phosphoinositide 3-kinase (PI3K) inhibitor, commonly known as wortmannin (Wtmn). This is very first time we are reporting the production of Wtmn from P. radicum. In addition to its previously discovered anticancer properties, the broad spectrum antifungal property of Wtmn was re-confirmed using various fungal strains. Virtual screening was performed through molecular docking studies against potential antifungal targets, and it was found that Wtmn was predicted to impede the actions of these targets more efficiently than known antifungal compounds such as voriconazole and nikkomycin i.e. 1) mevalonate-5-diphosphate decarboxylase (1FI4), responsible for sterol/isoprenoid biosynthesis; 2) exocyst complex component SEC3 (3A58) where Rho-and phosphoinositide-dependent localization is present and 3) Kre2p/Mnt1p a Golgi alpha1,2-mannosyltransferase (1S4N) involved in the biosynthesis of yeast cell wall glycoproteins). We conclude that Wtmn produced from P. radicum is a promising lead compound which could be potentially used as an efficient antifungal drug in the near future after appropriate structural modifications to reduce toxicity and improve stability.

Spectroscopic probe of atomically thin domains of CVD-grown MoSe2 - Singh, Vineeta; Late, Dattatray J.; Rath, Shyama (AIP Conference Proceedings, 2020)
Since the discovery of graphene, two-dimensional Layered Transition Metal Dichalcogenides (TMDCs) such as MoS2, MoSe2, and WS2 having a tunable bandgap, have emerged as one of the most stable classes of materials making them attractive for various applications. We have investigated the growth mechanism and shape evolution of various domains of CVD-grown MoSe2 on insulating substrates by spectroscopic techniques. The different morphologies were analyzed using Raman and photoluminescence spectroscopies. The transformation from the precursor MoO3 to MoSe2 is found to depend on a number of growth parameters and experimental conditions.

Tunable light emission from chemical vapor deposited two-dimensional MoSe2 by layer variation and S incorporation - Singh, Vineeta; Late, Dattatray J.; Rath, Shyama (Journal of Vacuum Science & Technology A, 2020)
Mono- and few-layer thick MoSe2 and MoSxSe2-x domains were grown on insulating SiO2/Si substrates by chemical vapor deposition. Scanning electron microscopy and optical contrast images were used to determine the domain size and morphology. The structure, crystallinity, and the thickness (number of layers) of the as-synthesized domains were determined from Raman spectroscopy. The light emission was determined from photoluminescence (PL) spectroscopy. The PL emission started appearing only in domains having four layers or less, with the intensity increasing as the number of layers decreased. The PL peak position varied between 1.48eV (similar to 838nm) for four layers to 1.55eV (similar to 800nm) in the monolayer limit. Sulfur incorporation was done to enable a further tunability of the bandgap. The monolayer bandgap changed from 1.55eV for MoSe2 to 1.64eV (similar to 756nm) for MoS0.32Se0.68. The other effect of S incorporation was the formation of larger area domains in the alloy as compared to binary MoSe2 with an improvement in the structural properties, thus providing a pathway to improve the properties of two-dimensional semiconductors by mixing of two materials with similar atomic arrangements.